The ‘New Turkey’ in the Broader Middle East
XIII, 282 p. 3 illus.
Keywords: This book offers a fresh rethinking of Turkish foreign policy under the Justice and Development Party (AKP), drawing on both mainstream and critical approaches within International Relations (IR) theory. Through a series of region-specific case studies—including Turkey’s evolving policies toward Syria, Iraq, Israel, the Gulf, and the Eastern Mediterranean—it explores the complex interplay of domestic, regional, and global drivers that shape foreign policy choices. The chapters engage with diverse theoretical perspectives such as Neo-Realism, Constructivism, Neo-Marxism, Critical Geopolitics, and Ontological Security. The contributors critically assess how well-established IR frameworks account for Turkey’s foreign policy behaviour in a shifting international landscape. In doing so, they test not only the boundaries of conventional theory but also contribute to the development of more nuanced, context-sensitive approaches to foreign policy analysis. Accessible to both scholars and general readers, this book enriches IR scholarship while providing new perspectives on Turkey’s shifting role in a transforming Middle East. Dr Zenonas Tziarras is a Lecturer in the Department of Turkish and Middle Eastern Studies at the University of Cyprus. He holds a PhD in Politics and international Studies from the University of Warwick, UK, with a focus on Turkish Foreign Policy under the Justice and Development Party (AKP). Zenonas attained a BA in Mediterranean Studies from the University of the Aegean, Greece, and an MA in International Relations and Strategic Studies from the University of Birmingham, UK. Dr Oğuzhan Göksel is Associate Professor of Political Economy at Marmara University, Turkey. He is also the Editor-in-Chief of New Middle Eastern Studies journal based in the UK. He completed his multi-disciplinary Ph.D. degree in Political Science and Political Economy at Durham University, UK in 2015.